The villas of the eastern Adriatic and Ionian coastlands - Bowden, William (Cambridge University Press, 2018)
This paper examines the Roman villas of the coastal regions of the Ionian and eastern Adriatic seas, covering their development from the early Imperial period until late antiquity.